Proceedings of the 1995 International Symposium on Low Power Design - ISLPED '95 1995
DOI: 10.1145/224081.224111
|View full text |Cite
|
Sign up to set email alerts
|

Transistor sizing for minimizing power consumption of CMOS circuits under delay constraint

Abstract: We consider the problem of transistor sizing in a static CMOS layout to minimize the power consumption of the circuit subject to a given delay constraint. Based on our characterization of the short circuit power dissipation of a CMOS circuit we show that the transistors of a gate with high fan-out load should be enlarged to minimize the power consumption of the circuit. We derive analytical formulation for computing the power optimal size of a transistor and isolate the factor aecting the power optimal size. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Methods of automating transistor sizing for timing optimization were proposed in [3,[10][11][12][13][14][15][16], but many of them focus on static CMOS circuits and technologies using multiple threshold voltages. TImed LOgic Synthesizer (TILOS) [10] presented an algorithm of iteratively sizing transistors by a certain factor in the critical path.…”
Section: Previous Workmentioning
confidence: 99%
“…Methods of automating transistor sizing for timing optimization were proposed in [3,[10][11][12][13][14][15][16], but many of them focus on static CMOS circuits and technologies using multiple threshold voltages. TImed LOgic Synthesizer (TILOS) [10] presented an algorithm of iteratively sizing transistors by a certain factor in the critical path.…”
Section: Previous Workmentioning
confidence: 99%
“…In many design scenarios, circuit delay is determined based on system-level considerations, and hence during optimization, one must minimize energy under user-specified timing constraints. Indeed, much of the published literature focuses on this problem, although authors have referred to it as minimizing power (calculated under a fixed clock frequency) under a given delay constraint (see for example [12] [153] [139]). To set the terminology straight, these works are minimizing energy under a delay constraint.…”
Section: Towards a Useful Guide For Making Design Trade-offsmentioning
confidence: 99%
“…In [12], the problem of transistor sizing in a static CMOS layout to minimize the capacitive plus short circuit power dissipation. It is shown that the power-optimal size for the transistors in a gate that is driving a given load, can be larger than minimum size.…”
Section: Transistor and Gate Sizingmentioning
confidence: 99%
“…[4,5,6]. Gate sizing has been utilized not only for delay optimization but also for power optimization [7,8,9,10]. The main idea of previous approaches for power reduction is to optimize the amount of capacitive load [7,8] or the amount of capacitive load and short-circuit current [9,10] based on the transition activity information obtained beforehand.…”
mentioning
confidence: 99%